Optimizing Financial Management Behavior Through Financial Literacy and Inclusion: The Strategic Role of Financial Self-Efficacy - MANDALA, I Gusti Ngurah Agung Kepakisan; PUTRI, Putu Yudha Asteria; PRILIANDANI, Ni Made Intan (Journal of Governance, Taxation and Auditing, 2025)
Financial self-efficacy reflects an individual’s confidence in managing finances, utilizing financial services, and believing in their ability to achieve long-term financial goals. This study aims to examine the influence of financial literacy and financial inclusion on financial management behavior, with financial self-efficacy serving as a mediating variable. Employing a quantitative approach, the study involved a population of 2,411,234 active customers from Lembaga Perkreditan Desa (LPD). A total of 384 respondents were selected using the Krejcie and Morgan formula through a non-probability sampling method with purposive sampling techniques. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) version 4.0 to assess both direct and indirect effects. The results indicate that financial literacy and financial inclusion have a significant positive impact on financial management behavior. Additionally, both variables significantly and positively influence financial self-efficacy. Furthermore, financial self-efficacy effectively mediates the relationship between financial literacy and financial inclusion toward financial management behavior. It implies that enhancing financial literacy and expanding financial inclusion, when accompanied by strengthening individuals' confidence in their financial capabilities, can lead to more optimal financial management behavior, particularly within LPDs currently facing financial health challenges.